Augmented HLL Riemann solver including slope source term for 1D mixed pipe flows - Shangzhi Chen (IWA Publishing, 2021)
In this paper, the augmented version of finite volume Harten–Lax–van Leer (HLL) solver, including source terms, is extended to free-surface and pressurized mixed pipe flows over complex and frictional topography. This augmented HLL Riemann solver is employed for the flux approximation at the cell interface, where source terms are split into two parts based on the wave propagation speed. The friction term is treated using a splitting implicit method to maintain stability over dry beds. The Preissmann slot method is adopted to reproduce pressurized flow in the conduit. The performances of the numerical model are investigated by several numerical tests and compared with existing methods showing clear improvements. HIGHLIGHTS An augmented HLL Riemann solver is extended to mixed pipe flows over complex topography.; Superiority simulating steady flows over complex topography with different hydraulic flow regimes.; Capability simulating transient dambreak pipe flow, including wetting or drying front and the calculation of the friction term.;